Immigrants' information experiences: an informed social inclusion framework. Issue 4 (2nd October 2018) - Beretta, Paola; Sayyad Abdi, Elham; Bruce, Christine
ABSTRACT: This paper reviews research related to immigrants' information experience. It identifies key themes in the literature associated with immigrants' engagement with information. The review suggests that immigrants: (a) have identified information needs; (b) tend to rely on both social networks and the Internet as sources of information; and (c) face certain obstacles to information access. The review also highlights the importance of culturally appropriate information and emphasises the role of information and libraries as key components of social inclusion. As an outcome of this analysis, these themes become key components of an evidenced-based 'informed social inclusion framework' that defines the role of information in immigrants' settlement journey towards social inclusion. Through providing a holistic portrait of information research within the migration context, the framework innovatively introduces information as one of the inseparable aspects of the multidisciplinary domain of migration studies. The framework is intended to be used as a guide to inform both research directions in information-focused migration studies, and the professional practice of libraries and other information agencies serving immigrant communities.